Underground Management In Agrarian Law Reform In Indonesia - Yayan Dimas Ageng; Misranto; Sunardi (UNIVERSITAS PAKUAN, 2026)
This study aims to analyze the regulation of management and basement use permits in agrarian law reform in Indonesia, examine their conformity with the principles of national agrarian law, and identify the legal consequences arising from their use. The main problem lies in the lack of a comprehensive and integrated regulation regarding the basement as a legal object, thus causing legal uncertainty and potential disputes. The type of research used is normative legal research with an analytical descriptive approach, using secondary data through literature studies and qualitatively analyzed. The results of the study show that the regulation of basements is still oriented to the concept of two-dimensional in agrarian law, so it has not been able to accommodate the development of the use of three-dimensional space. In addition, there is no harmonization with the principles of social function, justice, and legal certainty, as well as the weak fragmented licensing system, causing various legal consequences both civilly, administratively, and environmentally. Therefore, agrarian law reform is needed that recognizes the basement as a separate legal object and builds an integrated licensing system to ensure legal certainty and sustainable development. Keywords: Basement, Agrarian Law, Legal Certainty, Integrated Licensing, Legal Reform.